Influence of Hydrogen Peroxide On Liquefied Petroleum Gas (LPG) Performance - Muhammad Saad, Khan; Zulkafli, Hassan; Iqbal, Ahmed (2009)
The objective of this study is to investigate the effects of hydrogen peroxide (H2O2) on the combustion enhancer and performance of liquefied petroleum gas (LPG) on spark ignition engines. LPG has a simpler hydrocarbon structure than conventional fuels. H2O2 is recently reported as a renewable fuel and to be a low-emission high-quality fuel replacement. The addition of H2O2 at various wt. percentage concentrations in to LPG at mixture (LPG/H2O2) form will be used for the experiments and measurements can be made to study the performance, combustion, and emissions characteristics. The performance of in starting from lean LPG until obtaining a better composition can reduce the LPG fuel consumption. The theory behind this concept is that the addition of hydrogen peroxide can extend the lean operation limit, improve the lean burn ability, decrease burn duration and controlling the exhaust emission by reducing green house gaseous.